A Framework for Using GPS Data in Physical Activity and Sedentary Behavior Studies. Issue 1 (January 2015) - Jankowska, Marta M.; Schipperijn, Jasper; Kerr, Jacqueline
<x xml:space="preserve">Abstract</x> Global Positioning Systems (GPS) are applied increasingly in activity studies, yet significant theoretical and methodological challenges remain. This article presents a framework for integrating GPS data with other technologies to create dynamic representations of behaviors in context. Using more accurate and sensitive measures to link behavior and environmental exposures allows for new research questions and methods to be developed.